Using the Technology Acceptance Model (TAM) in Understanding the Preschool Teachers in Palestine Technology' Acceptance during the COVID-19 pandemic - Ahmad, Nafiz A.Ali; Zabadi, Abdelrahim M. (Eximia, 2022)
One of the long-term lessons from the school closures is that remote education has become a necessary reaction as a precautionary measure to prohibit the diffusion of the global epidemic "COVID-19 ". This requires preschool teachers to adapt rapidly to remote education as well as accept educational technologies. Research on the preschool teachers’ technology acceptance supplies evidence to improve their intention to utilize educational technology in emergency remote teaching. In the previous literature, the TAM is utilized broadly to test the process of technology acceptance by individuals. When the findings were evaluated, it can be stated that the participants' behavioral intention is medium to a high level. Perceived usefulness is influenced by job relevance and perceived ease of use. Also, computer self-efficacy and perceptions of external control are the positive factors toward perceived ease of use. Finally, perceived usefulness and perceived ease of use are direct significant predictors of preschool teachers’ behavioral intention. It is believed that the findings of the current study present a strong guide for the applicability of the TAM to a sample of Palestinian preschool teachers under contingency situations. These findings highlighted some probable paths for interventions purposed at improving preschool teachers’ acceptance of educational technology.